The Feasibility of Online Module with ICARE Learning Model Flow Based on Ubiquitous Learning Class - Hanizar, Evi; Triwahyuni, Eges; Pramana, Atan (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2024)
Online learning started with the emergence of Internet technology and has been increasingly used during the COVID-19 pandemic. However, it has raised many problems, such as limitations in presenting material (monotonous and uninteresting), building activeness, and difficulty creating interaction between lecturers and students and between students. Moreover, online learning is more stressful than regular classroom sessions because students have to study alone. The absence of clearly structured learning steps makes it difficult for them to focus. Therefore, this research aims to develop an independent online learning module based on ubiquitous classrooms with a structured and systematic flow called Introduce, Connect, Apply, Reflect, and Extend (ICARE). Furthermore, it determines the eligibility of the module using an ADDIE design for education, which consists of analysis, design, development, implementation, and evaluation. All stages resulted in an eligible online module with an u-learning class ICARE flow in the Learning Media course.